Comparative analysis of medieval Georgian and European medical treatises and remedies - Tea Tsitlanadze; Beka Kvatchadze; Andro Gogoladze (Історія науки і техніки, 2025)
The practice of medicine in Georgia has its roots in antiquity and is deeply intertwined with the medical traditions of ancient Greece and Rome. This rich scientific heritage is clearly reflected in early medieval Georgian medical traditions. In medieval Georgian historical writings contain specialized medical texts and treatises, demonstrating the advanced state of medical knowledge at the time. Among these texts, the 11th-century Georgian medical text Ustsoro Karabadini (“Incomparable Medical Handbook”) holds particular significance as an original Georgian medical treatise incorporating not only Georgian medical expertise but also insights from both ancient and medieval European medical traditions. The parallels between this text and Western European medical treatises are apparent from the very beginning. The text incorporates the Hippocratic and Galenic concept of the four humors, outlining the ailments linked to each humor and their respective treatments. Additionally, Ustsoro Karabadini offers health recommendations based on seasonal changes, describing the challenges the human body faces throughout the year and providing guidance on overcoming illness and maintaining proper nutrition. The treatise also includes noteworthy insights into pregnancy, gender prediction, and childcare practices. It places particular emphasis on a balanced diet, detailing the appropriate consumption of plant- and animal-based foods. A notable section is dedicated to the medicinal benefits of wine, a subject deeply ingrained in both Georgian and European traditions, where it was closely associated with daily life and sacred significance of Christian rituals. The analysis of these treatises clearly demonstrates that, similar to Europe, Georgia developed agricultural practices, particularly the cultivation of vines and cereals. Historical and archaeological research confirms that the tradition of cultivating grapevines and wheat in the Caucasus region dates back to the Neolithic era. The Georgian territory is considered one of the oldest centers of viticulture and wheat cultivation. An analysis of medical treatises reveals that prolonged engagement with these agricultural practices both in the Georgian and broader European contexts contributed to the discovery of similar medicinal properties associated with these crops. A comparative analysis of Ustsoro Karabadini and European medical treatises suggests that Georgian medicine was significantly influenced by both European and ancient (Greek-Roman) medical traditions, sharing many common characteristics with them.